Reprovados, indisciplinados, fracassados: as micro-relações de insucesso escolar na perspectiva do "aluno problema" - Silva, Ana Paula Ferreira da (2009)
This research focused on the understanding of questions related to failure, indiscipline and school dropouts in the view of the poor student, i.e., the student that effectively lives the experience of not adapting to the formal system of public education. Taking the micro-sociological approach (Collins, 1988, 1981) as the theoretical-methodological basis and the anthropological tools (Geertz, 2008, 2001 e Velho, 2003, 2002, 1997) that ethnographic researches (Woods, 1999, 1987) provides us, I decided to observe the school micro-relationships in six different classes of the elementary school in a Public School of São Paulo, located in the northwest region of the city, between years 2006 and 2008. Such decision assured that my presence was gradually ignored, allowing to register in my Field Notes (Cubides, Laverde e Valeria, 1998) the closest reality of the personal and school relationships observed in that place. The notes related to the sixty eight visits, plus the interviews with the students of 3rd and 4th grade of the Project classes in the morning period of 2008 composes the Field Notes, attached to this research. The data were organized in central questions, under two main basis: one related to Projeto Intensivo do Ciclo I (PIC), and other related to the way students perceive the schooling process and their own interactions among peers and with teachers. These questions have been discussed based on the theoretical references proposed by Lahire (2004), Dubet (2008, 2003b), Charlot (2002), Certeau (1994), Velho (2003), Goffman (2004, 1988) e Elias e Scotson (2000). Considering that the main purpose was to understand the school micro-relationships related to failure, the observations sought to find evidences of practices that help or complicate the learning process and the student development, such as the criterias used by those identified as trouble-students to distinguish themselves or to corroborate their belonging to this group. The analyses have shown that part of the students, in addition to establishing tactics in order to minimize the exposure of its weaknesses in front of the group and even teachers, considers itself responsible for its own failure, at the same time that identifies, in the school practices and in the teachers attitudes, important aspects that can enable its development in school